2007
DOI: 10.1111/j.1464-410x.2006.06662.x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic augmentation cystoplasty: a comparison between native ileum and small intestinal submucosa in the porcine model

Abstract: assessed and then the pigs were killed; the bladders were harvested and examined histologically. RESULTSIn all, 12 of 14 pigs completed the 6-week survival period; two pigs from the SIS group died from urinary ascites secondary to anastomotic leaks at the cystoplasty site. There were no complications in the ileal augmentation group. The operative duration was similar in both groups. The bladder capacities increased significantly in both groups, although more reliably in the native ileum group. In two pigs in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
(23 reference statements)
0
8
0
1
Order By: Relevance
“…This temporal mismatch shifts in favour of the degradation rate and greatly contributes to postoperative complications such as poor compliance, decreased bladder capacity and significantly impaired renal function. Complications of this nature may persist unabated until the remodelling response has been completed after 90–120 days [7], [19]. Preliminary studies in our laboratory have demonstrated that an increase in ECM surface-area relative to its intended bladder defect may prevent these complications by increasing the storage reservoir of the bladder [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This temporal mismatch shifts in favour of the degradation rate and greatly contributes to postoperative complications such as poor compliance, decreased bladder capacity and significantly impaired renal function. Complications of this nature may persist unabated until the remodelling response has been completed after 90–120 days [7], [19]. Preliminary studies in our laboratory have demonstrated that an increase in ECM surface-area relative to its intended bladder defect may prevent these complications by increasing the storage reservoir of the bladder [9].…”
Section: Discussionmentioning
confidence: 99%
“…A paucity of literature is available on AC with ECMs, however one recent study by Wang et al . assessed AC with autogenous ileum and small intestinal submucosa (SIS) in a porcine model [19]. Findings from their study demonstrated greater capacity increases in bladder's augmented with ileum (211 ml) compared to SIS (144.3 ml) after a 6 week experimental time period.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors described the appearance of adhesions during the macroscopic post-mortem examination [13,20]. In this work only few mild cases of adhesions were found, mostly to the omentum and rectum.…”
Section: Discussionmentioning
confidence: 92%
“…Bladder reconstruction with SIS has demonstrated regeneration of transitional epithelium, smooth muscle and nerves in various different animal models. [5859] Although the initial results have been promising, long-term results have been poor. This is due to the complications such as fibrosis resulting in graft shrinkage, graft incrustation or infection.…”
Section: Alternative Optionsmentioning
confidence: 99%